Sociolinguistic Dynamics of Minangkabaunese Language: Shifting Patterns and Preservation Efforts in Domestic Contexts - Elvi Susanti; Dona Aji Karunia Putra; Muhammad Zainal Muttaqien; Didah Nurhamidah (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2026)
One of the weaknesses in sociolinguistic studies in Indonesia is the lack of empirical research that specifically discusses the factors that influence the decline in Minangkabaunese language use. Therefore, this study aimed to describe the realization of Minangkabaunese language use in the family as well as the community's perception of the importance of preserving this language. This research used a qualitative approach with mixed methods. Data were collected through observation, online questionnaires (google form), in-depth interviews, and focus group discussions. The results of this study reveal that the use of Minangkabaunese language in family communication has shifted significantly. The main factors causing this include the preference for Indonesian as the main language in communication between family members, both in husband-wife relationships and between parents and children. Although some respondents still use Minangkabaunese language for reasons of communication effectiveness, emotional intimacy, and cultural preservation, the more dominant proportion of Indonesian language use indicates that Minangkabaunese language is facing a threat of decline in the domestic setting.